THE SIGNIFICANCE OF YOUTH SUPPORT IN THE PROCESS OF SOCIAL PROTECTION OF THE POPULATION IN UZBEKISTAN - Rahmonov Elyor Abdullajonovich; Mukhsin Moydinovich Kholmatov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article highlights the formation of a youth employment system in Uzbekistan, the periodicity of reforms, the strengthening of the legal framework, and the fact that small businesses and private entrepreneurship are key factors in ensuring youth employment.